Cytotoxic effects of different concentrations of chlorhexidine - Souza, Lorena Brito de [UNESP]; Aquino, Sabrina García de [UNESP]; Souza, Pedro Paulo Chaves de [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (My University, 2007)
Purpose: To evaluate the cytotoxic effects of different concentrations of Chlorhexidine (Chx) to the odontoblast cell line MDPC-23. Methods: The odontoblast-like cells were seeded (30,000 cells/cm 2) in 60 wells of 24-well dishes and then incubated in contact with the following experimental and control solutions: Group 1: 0.0024% Chx; Group 2: 0.004% Chx; Group 3: 0.02% Chx; Group 4: Phosphate buffer saline solution (PBS, negative control); and Group 5: 0.06% H 2O 2 (positive control). Cell metabolic activity was measured by MTT assay and the cell morphology was analyzed by SEM. Results: The cytotoxic effects of Chx are dose-dependent. The reduction in the cell metabolism for Groups 1, 2, and 3 was 24.8%, 29.9% and 70.8%, respectively. No statistical difference was observed between the Groups 1 and 2 in which no significant cell morphology changes occurred. Consequently, it was concluded that 0.02% Chx solution presents high cytotoxicity to the odontoblast-like cells MDPC-23. On theother hand, 0.0024% and 0.004% Chx causes slight cytopathic effects to the cultured cells.
Keywords: buffer; chlorhexidine; coloring agent; diagnostic agent; hydrogen peroxide; oxidizing agent; sodium chloride; tetrazolium; thiazole derivative; thiazolyl blue; topical antiinfective agent; unclassified drug; animal; cell adhesion; cell line; cell membrane; cell shape; comparative study; dose response; drug effect; metabolism; mouse; odontoblast; pathology; ultrastructure; Animals; Anti-Infective Agents, Local; Buffers; Cell Adhesion; Cell Line; Cell Membrane; Cell Shape; Chlorhexidine; Coloring Agents; Dose-Response Relationship, Drug; Hydrogen Peroxide; Mice; Odontoblasts; Oxidants; Sodium Chloride; Tetrazolium Salts; Thiazoles